1985
DOI: 10.3109/00016348509155157
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐thromboglobulin in Pre‐eclampsia

Abstract: Beta-thromboglobulin was tested in blood and urine in a study group of pre-eclamptic patients. The control group comprised a subgroup of normal non-pregnant women and a second subgroup of normal pregnant women. The results of the plasma beta-thromboglobulin blood test revealed no significant difference between the groups, whereas the urine of the pre-eclamptic group showed a significantly increased concentration of beta-thromboglobulin. This difference may reflect renal involvement in the pre-eclamptic patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…β-TG level was also comparable between 2nd trimester, 3rd trimester pregnant women and non-pregnant women. This finding is in accordance with previous observations by Leiberman et al (1985) and Romero et al (1988). They have also reported that gestational age, labor, and puerperium did not affect plasma β-TG concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…β-TG level was also comparable between 2nd trimester, 3rd trimester pregnant women and non-pregnant women. This finding is in accordance with previous observations by Leiberman et al (1985) and Romero et al (1988). They have also reported that gestational age, labor, and puerperium did not affect plasma β-TG concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, we found that in severe preeclampsia the bleeding time was markedly prolonged, not associated to the slight reduction of the platelet count observed in this group of patients. Previous studies in preeclamptic patients havc shown an early platelet activation, which is evidenced by the release of B-thromboglobulin and platelet factor 4 (1, 10, 11, 13,13,14), and by the decrease of the endogenous serotonin in the platelet (1 5); moreover, thromboxane released by t h e platelets enhances platelet aggregation and maintains the imbalance with prostacyclin, which is a ugmented in preeclampsia (16,17). These functional modifications, both in platelets and in endothelial cells, suggested by different markers of the endothelial cell injury reported in preeclatnpsia ( 18, 19,20,21,22), may have a role in the bleeding time modifications in preeclampsia.…”
Section: Discussionmentioning
confidence: 99%